2019
DOI: 10.1542/peds.2018-3640
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Noninvasive Carbon Dioxide Monitoring in Neonates: From Theory to Standard of Care

Abstract: Ventilatory support may affect the short- and long-term neurologic and respiratory morbidities of preterm infants. Ongoing monitoring of oxygenation and ventilation and control of adequate levels of oxygen, pressures, and volumes can decrease the incidence of such adverse outcomes. Use of pulse oximetry became a standard of care for titrating oxygen delivery, but continuous noninvasive monitoring of carbon dioxide (CO2) is not routinely used in NICUs. Continuous monitoring of CO2 level may be crucial because h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…It is a method that can be used in invasive and non-invasive ventilation and even in unventilated patients, while the expired CO 2 is used in IMV. 8 One criteria of the review were to include the newborns submitted to IMV, which can have affected the smaller number of studies with a transcutaneous approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a method that can be used in invasive and non-invasive ventilation and even in unventilated patients, while the expired CO 2 is used in IMV. 8 One criteria of the review were to include the newborns submitted to IMV, which can have affected the smaller number of studies with a transcutaneous approach.…”
Section: Discussionmentioning
confidence: 99%
“…Transcutaneous measurement of CO 2 (tcCO 2 ) is based on the diffusion of CO 2 through body tissues, which can be detected by a sensor positioned on the skin surface. 8 Capnometry quantifies the level of CO 2 throughout the respiratory cycle by means of its concentration in exhaled air at the end of exhalation (PetCO 2 ). It is used for successful verification of orotracheal intubation, assessment of pulmonary circulation and respiratory status, and optimization of mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…PtcCO 2 monitoring is now standard of care in neonatology (Hochwald et al. 2019). PtcCO 2 can be used as a surrogate for PaCO 2 to calculate dead space ventilation in sedated patients receiving mechanical ventilation (Lakshminarayana et al.…”
Section: Discussionmentioning
confidence: 99%
“…revealed that CO2 fluctuations are associated with changes in cerebral oxygenation and electrical activity in the first 72 h of life in preterm infants [ 46 ]. Therefore, to avoid significant hypocarbia and hypercarbia, and to prevent related brain injury, it might be prudent to incorporate continuous non-invasive CO2 monitor into standard of care in the ventilated ELBW infants [ 47 ].…”
Section: Non-invasive Co2 Monitormentioning
confidence: 99%